Nurses’ satisfaction with the implementation of a deglutition assessment procedure: cross-sectional study - Teixeira, Filipe; Sentieiro, Adriana; Cunha, Andreia; Pires, Edgar; Silva, Miriam; de Deus, Cátia (Salud Integral y Comunitaria, 2025)
Introduction: Dysphagia affects around 40 million people in Europe and increases the risk of aspiration in stroke patients by 4.08 times, making it essential to assess patients’ swallowing abilities. At the Professor Doutor Fernando Fonseca Hospital of the Amadora-Sintra Local Health Unit, the Volume-Viscosity Clinical Exploration Method is used. In January 2024, the swallowing assessment procedure was published. This study aims to identify the degree of satisfaction of nurses from the Neurology Service and the Adult Emergency Service at HFF regarding the implementation of the swallowing assessment procedure. Methods: This is a cross-sectional study. A specific questionnaire was developed. The Qualtrics online platform was used to collect the data between June 3 and July 3, 2024. Quantitative data analysis was conducted. Results/Discussion: 38,46% of nurses working in these services responded to the questionnaire. The average age of the participants was 31,86 years old, with the majority working in the Adult Emergency Service. Satisfaction with the implementation of the procedure was 76,36% while satisfaction with training was 81,25%. The reported benefits of implementing the procedure were: simplicity and easy application (75,51%), easy interpretation of the result (85,71%) and facilitating the provision of an adequate diet (89,8%). These findings are evident in other studies on this topic. Conclusions: Nurses expressed satisfaction with the implementation of the procedure, as it enhances the quality of nursing care and facilitates patients’ functional readaptation.